Addressing Barriers to Success in Accounting Education: Exploring the Role of ODeL Institutions in Facilitating Meaningful Access and Achieving Success for Marginalised Groups - Musundwa, Sedzani; Masela, Nkosinathi; Chikutuma, Chisinga; Enwereji, Prince Chukwuneme; Hlongoane, Moses; Tshehla, Makgopa (Journal of University Teaching and Learning Practice, 2025)
The evolution of Open Distance e-Learning (ODeL) institutions has significantly broadened access to higher education for historically marginalised (equity) groups. However, despite these advancements, persistent challenges undermine student success, particularly in accounting education, where rigorous academic demands intersect with socioeconomic and technological barriers. This study explores how ODeL institutions, focusing on the University of South Africa (UNISA), can enhance meaningful access and improve success rates for students from disadvantaged backgrounds. Guided by Moore’s Transactional Distance Theory, the study employs a qualitative approach, incorporating interviews with students and educators to examine the barriers to academic achievement. Key findings highlight administrative inefficiencies, communication breakdowns, technological limitations, and programme rigidity as significant impediments. The paper concludes by offering targeted recommendations for institutional reforms, including enhanced technological infrastructure, improved administrative support, and structured academic interventions to foster student autonomy and engagement. Addressing these issues is crucial for ensuring that ODeL institutions fulfil their social justice mandate and contribute to the transformation of the accounting profession.